GAPS IN SEXUALITY EDUCATION IN THE CURRICULUM DOCUMENT OF SANTO ANDRÉ/SP (Interdisciplinary Studies Journal, 2026)
This research project analyzed the Curriculum Document of the Municipal Education Network of Santo André (2019) regarding guidelines for Sex Education (SE) work with children in elementary school (grades 1-5) in the public school system. Our main problem was the concealment of gender and sexuality in the municipality's official materials, a situation also observed at the federal level, with the National Common Curriculum Base (2017). The main hypothesis of the research was that some of these themes would be incorporated into the school curriculum through Informal Sex Education (Figueiró, 2017), leveraging everyday school situations and students' expressions. As a result, we highlight that even though the Curriculum Document does not explicitly address certain terms, it is possible to find gaps in some curricular components, mainly Geography and History, since they use words such as diversity, difference, identity, community, and respect, which are essential for discussions in Sex Education.
Keywords: Curriculum Document; Santo André; Sex Education; Informal Sex Education